Impact of thermocycling on surface roughness, microhardness and optical properties of three different lithium disilicate ceramics - Ahmad M. Al-Thobity; Abdulkareem M. AlOtaibi; Abdulrahman E. Alhumaidan; Ahmed A. Aldossary; Intisar Ahmad Siddiqui; Mohamed Ahmed Helal; Abdulmohsen Alsalman (Saudi Dental Journal)
Objectives: This investigation was carried out to examine the influence of thermocycling aging on the surface roughness (Ra, µm), color parameters (L*, a*, b*), lightness change (ΔL*), chroma change (ΔC*ab), color change (ΔE), and microhardness (VH) of three lithium disilicate ceramics. Materials and methods: Forty-five specimens were prepared from three lithium disilicate materials (n = 15)—e.max CAD (EC), e.max Press (EP), and GC Initial LiSi Press (LP) ceramics—with dimensions of 6.0 × 1.2 × 16.0 ± 0.2 mm following the manufacturers’ instructions. All specimens were exposed to 5000 thermal cycles with bath temperatures ranging between 5 °C and 55 °C. Data of surface roughness, color parameters, and microhardness were obtained using an optical profiler, a spectrophotometer, and a Vickers hardness tester, respectively. One-way ANOVA, a post-hoc Tukey’s test, and a paired sample t-test were implemented for statistical analysis (p ≤ 0.05). Results: For surface roughness, insignificant differences were reported between the materials either before or after thermocycling (p > 0.05) while each material displayed a significant increase after being subjected to thermocycling (p < 0.05). For color parameters, LP showed significantly lower L* and b* after thermocycling while EC presented a significant reduction in a* in comparison with other materials (p < 0.05). EP showed a significant decrease in ΔL*, ΔC*ab and ΔE compared with other materials (p < 0.05). Regarding microhardness, LP showed significantly increase value in comparison with other materials (p < 0.05). Conclusions: Thermocycling had a major impact on the surface roughness, microhardness and optical characteristics of the tested materials. E.max Press displayed less changes in (ΔL*), (ΔC*ab) and (ΔE), while GC LiSi Press had better behavior in terms of microhardness.